Jersey : Financial Sector Assessment Program Update; Detailed Assessment of Observance of AML/CFT. (IMF Staff Country Reports; Country Report, 2009)
Jersey has put in place a comprehensive and robust Antimoney Laundering/Combating the Financing of Terrorism (AML/CFT) legal framework with a high level of compliance with almost all aspects of the Financial Action Task Force recommendations. The paper discusses a Detailed Assessment of Observance of AML/CFT report on Jersey. Both money laundering and financing of terrorism are criminalized largely in line with the international standard, and Jersey has implemented the provisions effectively.